MANAGEMENT OF MIDWIFERY CARE IN TRANSVERSE LIE PREGNANCY AT SARFINA CLINIC IN 2026 - Ramadhani, Fitri; Pakpahan, Desi Mandayani; purba, Gracia angelina; Sinaga, Asnita; Sembiring, Sarfina (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Transverse lie is one of the abnormal fetal presentations that may increase the risk of maternal and neonatal complications during labor, including obstructed labor, umbilical cord prolapse, uterine rupture, and postpartum hemorrhage. Early detection and appropriate management are essential to prevent adverse outcomes. Objectives: This study aimed to describe the implementation of midwifery care for Mrs. S with a transverse lie pregnancy at Sarfina Sembiring Clinic in 2026. Methods: A case study design was employed using Varney’s Midwifery Management Approach. Data were collected through anamnesis, physical examination, obstetric examination using Leopold maneuvers, observation, and medical record review. Results: The examination revealed that the fetal head and buttocks were located on opposite sides of the maternal abdomen, with no presenting part entering the pelvic inlet, indicating a transverse lie presentation. Midwifery care included maternal and fetal monitoring, health education, counseling regarding pregnancy danger signs, psychological support, and referral for delivery management. The patient and family demonstrated a good understanding of the pregnancy condition and agreed to the referral recommendation. Conclusions: Comprehensive midwifery care enabled early identification of transverse lie presentation and facilitated timely referral for appropriate delivery management. Early detection, effective counseling, and referral are important strategies to reduce the risk of complications and improve maternal and neonatal outcomes.